Hydrological characterization of an urban watershed in Ceará using Geographic Information System – GIS (Research, Society and Development, 2022)
The impermeabilization process in cities has caused high surface runoff and, consequently, causing floods due to the inexistence and/or precariousness of drainage systems. Thus, this research aims to conduct a study about the surface runoff in an urban watershed in the city of Barro. For the delimitation of the basin an MDE from SRTM image, obtained by the TOPODATA project, was used. For the delimitation of the basin, contour maps, drainage network and slope map were elaborated. It was verified that the region presents drainage problems in the rainy season, however, the basin presents little tendency to flood. Showing that the problem caused in the region under study, does not come through the characterization of the watershed but by the absence of a drainage system in place, causing all water precipitated on the watershed to drain superficially.